2023
DOI: 10.1200/jco.22.00332
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab Plus Ipilimumab Versus EXTREME Regimen as First-Line Treatment for Recurrent/Metastatic Squamous Cell Carcinoma of the Head and Neck: The Final Results of CheckMate 651

Abstract: PURPOSE CheckMate 651 (ClinicalTrials.gov identifier: NCT02741570 ) evaluated first-line nivolumab plus ipilimumab versus EXTREME (cetuximab plus cisplatin/carboplatin plus fluorouracil ≤ six cycles, then cetuximab maintenance) in recurrent/metastatic squamous cell carcinoma of the head and neck (R/M SCCHN). METHODS Patients without prior systemic therapy for R/M SCCHN were randomly assigned 1:1 to nivolumab plus ipilimumab or EXTREME. Primary end points were overall survival (OS) in the all randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…The study randomized a total of 947 patients and, at a minimum follow-up of 27.3 months, did not find a statistically significant improvement in OS regardless of CPS score or HPV status when compared to the EXTREME regimen. However, grade 3 and 4 adverse events occurred in 28.2% of patients in the combination arm and 70.7% in the EXTREME arm [ 70 ]. Although CheckMate-651 did not meet its primary endpoint of OS, the combination arm demonstrated a more favorable safety profile.…”
Section: Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The study randomized a total of 947 patients and, at a minimum follow-up of 27.3 months, did not find a statistically significant improvement in OS regardless of CPS score or HPV status when compared to the EXTREME regimen. However, grade 3 and 4 adverse events occurred in 28.2% of patients in the combination arm and 70.7% in the EXTREME arm [ 70 ]. Although CheckMate-651 did not meet its primary endpoint of OS, the combination arm demonstrated a more favorable safety profile.…”
Section: Immunotherapymentioning
confidence: 99%
“…Examples include targeting IDO1 [ 74 ], TLR8 agonists [ 75 ], OX40 [ 76 ], and B7-H3 [ 77 ], the detailing of which are beyond the scope of this review. Major trials regarding ICIs and HPV-related OPSCC are demonstrated in Table 1 [ 51 , 63 , 65 , 66 , 67 , 69 , 70 , 71 , 72 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…Immunotherapy and more specifically check-point inhibitors (ICIs) have revolutionized the management of solid tumors but despite the great advancements, ICIs have been limited by a lack of ability to confidently identify patients who are likely or unlikely to positively respond to treatment 1 . A prime example is mucosal Head and Neck Squamous Cell Carcinomas (HNSCCs) where multiple studies have failed to show a benefit of ICIs over standard chemotherapy [2][3][4] . This failure is partially explained by the high inter-and intra-tumor heterogeneity of mucosal HNSCCs with different tumor microenvironments (TME) influenced by the location of primary site and etiology (i.e., HPV + vs HPV -) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The study population in CheckMate 651 included only patients with platinum-eligible disease (no prior platinum treatment or platinum treatment during curative-intent therapy recurrence or metastasis greater than 6 months after curative therapy) . Although not meeting its statistical boundary, this study demonstrated a convincingly favorable outcome for the primary end point, survival in the combination arm compared with the EXTREME regimen in patients with combined positive score (CPS) greater than 20, and for patients with CPS greater than 1, a secondary end point .…”
mentioning
confidence: 98%